The effect of internet on travel intermediaries in Malaysia (A case of a retail travel agent) / Wan Azhar Wan Yusof, Farhan Akma Nordin and Mazlina Mahdzar. - Wan Yusof, Wan Azhar; Nordin, Farhan Akma; Mahdzar, Mazlina (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2017)
Purpose - The purpose of this paper is to investigate the effect of Internet from perspectives of traditional intermediaries (travel agency). Internet offers customers with various tools to search info and purchase products/services directly from the suppliers. Therefore, the role and evolution of travel agencies nowadays become questionable. Design/methodology/approach - An interview was conducted with a travel agency in Malaysia to collect primary data for this qualitative research. Findings - Even though the effect of disintermediation is severe, there are still demands from the customer that felt the needs of travel agencies because of the personalized services, customizable packages, and also they felt more secure to purchase with the travel agencies.